The logic of scientific writing - Volpato, Gilson Luiz [UNESP] (My University, 2011)
In this work, I describe a logical method for scientific writing. Any decision made in this type of writing should be based on the logic of science and the rules of communication, as part of a creative discourse. I present some logical flaws (regarding journal classification, academic vs. nonacademic texts, and subjective inferences) and writing mistakes (in the structure of a paper and the writing style) that can undermine publication.
Keywords: Scientific writing; Scientific communication; Scientific publication; Science; Logic